Improvement to Production of Cassava as An Economic Potential of The Residents of Dawuhan Village - I. Ghozali; S. Zuhri; S. Zuhri (Nusantara Science and Technology Proceedings)
The potential of cassava tubers as a food ingredient that is widely available in Indonesia, especially the dawuhan village as a thematic KKN location that has abundant agricultural products and can be developed as processed products that have a higher economic value and is able to increase economic productivity for local villagers. Processed cassava products into cassava chips are products that have high market value, especially as products that can lift the image of the village to become a guided village with cassava chips that have a high flavor. The ability of rural communities to process products is still limited in terms of technology use and the ability to process these processed products to be more delicious, tasty and trendy. Utilization of production equipment such as chopper machines, slicing machines and a good packaging system can increase cassava chips processed products into products that have a high selling value and can be a source of income for the majority of rural communities, even later can encourage rural tourism of local specialties. The results of the application in the field can be produced that increasing production capacity and production quality can continue to be developed by utilizing these production tools and developing better packaging technology so that processed cassava chips products can compete with other products that have already developed.